AUTHENTIC LEARNING THROUGH AUDITING SOFTWARE IN LEARNING AUDITING : A MALAYSIAN UNDERGRADUATE PERSPECTIVE - Damien Iung Yau Lee; Sharon Cheuk Choy Sheung; Mohd Waliuddin bin Mohd Razali; Shamsul Anuar Bin Abd Rahim (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This paper examines whether auditing software provides students with motivation and interest, learning opportunities, critical thinking, and real-world exposure. The research was conducted on auditing classes under an undergraduate accounting program in a public university across three semesters from 2022 to 2024. A structured questionnaire was used to assess the student’s authentic learning experience. Our study providing valuable insights for educators, policymakers, and potential employer by highlighting the experiential authentic learning in a Malaysian university.